Second Generation of the Automated Cobas Amplicor HCV Assay Improves Sensitivity of Hepatitis C Virus RNA Detection and Yields Results That Are More Clinically Relevant - Doglio, Alain (American Society for Microbiology, 1999)
The first and second generations of the Cobas Amplicor HCV assay were compared among patients at risk of hepatitis C virus (HCV) infection. The second-generation test was found to be of greater sensitivity and of good specificity among clinical specimens containing HCV RNA of different genotypes. Finally, this new test is shown to predict the outcome of interferon therapy better.